A simple ESIPT combines AIE character "turn on" fluorescent probe for Hcy/Cys/GSH detection and cell imaging based on coumarin unit. (December 2022) - Ding, Ge; Wang, Xinchao; Luo, Derong; Meng, Suqi; Zhou, Linling; Fan, Yinjie; Ling-hu, Changxin; Meng, Jiangping; Si, Wantong; Chen, Quanzhou; Bi, Ruiming
Abstract: In view of crucial role of biothiols in various physiological processes, exploitation of convenient and efficient sensing method for the biothiols detection is of terrific scientific significance. Although recently some related work has been done, the application of fluorescent probes for rapid simultaneous detection of biothiols in both vivo and vitro has been rarely reported. In this work, we successfully designed and developed a simple fluorescent probe DEMCA-NBSC based on coumarin fragment, which presents remarkable emission enhancement and exhibits yellow-green fluorescence with a 365 nm UV lamp irradiation after addition of biothiols (Hcy/Cys/GSH), and the intensified emission response is ascribed to biothiols induced the cleavage of NBSC group to form a fluorescent compound DEMCA-OH, which exhibited a strong aggregation induced emission (AIE) property. It is worth mentioning that DEMCA-NBSC exhibits rapid response (within 3 min), high selectivity, outstanding sensitivity, lower the detection of limit (0.236 μM, 0.223 μM, 0.365 μM for Cys, GSH and Hcy, respectively) to biothiols, and DEMCA-NBSC possesses low toxicity and high sensitivity when used in biological systems, thus, it can successfully achieve rapid biothiols detection and intracellular imaging by difference in fluorescent signals. This probe provides an effective tool for the real-time detection of biothiols in both vivo and vitro. Graphical abstract: Image 1 Highlights: Designed a novel AIE "turn on" fluorescent probe DEMCA-NBSC for biothiols detection in both vivo and vitro. Detection abilities for biothiols with high sensitivity, specifity and lower limit of detection (LOD). The probe DEMCA-NBSC realized detection and recognition for biothiols with a rapid response time.